Phase II Trial of Angiotensin-(1-7) for the Treatment of Patients with Metastatic Sarcoma - Savage, Paul D. (Sarcoma, 2016)
Background. Angiotensin-(1-7) [Ang-(1-7)] is an endogenous antiangiogenic hormone with anticancer activity. In a phase I study of Ang-(1-7), two of three patients with metastatic sarcoma experienced disease stabilization. This phase II study examined clinical and biomarker outcomes for patients with metastatic sarcoma. Methods. Ang-(1-7) was administered by subcutaneous injection at a dose of 20 mg daily. If excessive toxicities occurred in the first cohort, a dose deescalation cohort was allowed. Blood samples were obtained to measure changes in biomarkers. Results. Treatment was well-tolerated and the dose deescalation cohort was not required. Plasma PlGF concentrations following treatment were not statistically significantly changed. A significant increase in plasma Ang-(1-7) was observed at 4 hours after injection. The median progression-free survival was 2.7 months (95% CI; 1.4 to 4.1 months), and the median overall survival was 10.2 months (95% CI; 5.3 to 18.3 months). Two patients with vascular sarcomas demonstrated prolonged disease stabilization of 10 months (hemangiopericytoma) and 19 months (epithelioid hemangioendothelioma). Conclusions. Ang-(1-7) at a dose of 20 mg daily was well-tolerated. This prospective phase II study failed to confirm the PlGF biomarker effect identified in the prior phase I study. Prolonged disease stabilization in hemangiopericytoma and epithelioid hemangioendothelioma may warrant further investigation.